2016
DOI: 10.1007/s11060-016-2163-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term visual outcomes of optic pathway gliomas in pediatric patients without neurofibromatosis type 1

Abstract: Sporadic optic pathway gliomas (OPGs) have been reported to cause more vision loss than OPGs associated with neurofibromatosis type-1, but long-term visual outcome data are limited. The purpose of this study was to report the visual outcomes of a cohort of pediatric patients with sporadic OPGs. This was a retrospective, cohort study at a tertiary care pediatric hospital and cancer institute. The study included all patients with sporadic OPGs evaluated from 1990 to 2014. The primary outcome was visual acuity at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 34 publications
2
31
2
3
Order By: Relevance
“…In our NF1 cohort, children with Dodge stage 3 tumours were seven times more likely to experience worsening VA and a poor final VA outcome despite treatment. Wan et al found that postchiasm sporadic OPGs were associated with a worse visual outcome for the less severely affected eye but not with the more severely affected eye 12. In our sporadic OPG cohort, posterior tumour extent was not found to be a significant prognostic factor.…”
Section: Discussioncontrasting
confidence: 69%
“…In our NF1 cohort, children with Dodge stage 3 tumours were seven times more likely to experience worsening VA and a poor final VA outcome despite treatment. Wan et al found that postchiasm sporadic OPGs were associated with a worse visual outcome for the less severely affected eye but not with the more severely affected eye 12. In our sporadic OPG cohort, posterior tumour extent was not found to be a significant prognostic factor.…”
Section: Discussioncontrasting
confidence: 69%
“…This finding resembles the endocrine results in the proton series reported by Greenberger et al 4 After irradiation, we observed a 1% rate of visual deterioration and a 2% rate of hearing loss, both of which compare favorably to outcomes reported after photon therapy in smaller series. [20][21][22] Recent studies have drawn attention to the risk of vasculopathy and brainstem necrosis after proton therapy. 9,23,24 In children undergoing photon therapy for LGG, the comparative data are modest.…”
Section: Freedom From Event (%)mentioning
confidence: 99%
“…15 Sporadic optic gliomas have been reported to cause more serious long-term visual impairment than those associated with neurofibromatosis type 1. 16 Changes in tumor size and extension and visual acuity would prompt tumor-directed therapy to preserve vision in the contralateral eye. 11,15 Any relation between optic glioma and MGDA has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%